Health Professions as Distinct Cultures in Interprofessional, Intercultural Clinical Placements: A Pilot Study Exploring Implications for Interprofessional Supervision - Eley, Diann S; McAllister, Lindy; Chipchase, Lucy; Strong, Jenny; Allen, Shelley; Davidson, Bronwyn (International Journal of Practice-based Learning in Health and Social Care, 2015)
This paper reports on a pilot study that incorporated discipline specific clinical skill development with intercultural and interprofessional education (IPE) experiences for eight health professions students on clinical placement in a Disability Program in Vietnam. The aim of this study was to examine students’ experiences of interprofessional work while in an intercultural learning environment. A mixed methods design explored student perceptions of their experiences and learning in an interprofessional and intercultural context using semi-structured interviews, the Readiness for Interprofessional Learning Scale (RIPLS) and the Cross-Cultural Adaptability Inventory (CCAI) pre- and post-placement. The quantitative measures were used as a means of individual feedback to student and to assist in the interpretation of the qualitative data. Interviews indicated that students agree on the importance of working interprofessionally but perceived adjustment to interprofessional supervision was more challenging than adjustment to the Vietnamese clinical culture. Students scored lowest on Professional Identity (RIPLS) and Personal Autonomy (CCAI). This study provides an adjunct approach to gaining insight into final year students’ perception of interprofessional work while in an intercultural learning environment. Our small sample size cannot imply student’s definitive attitudes toward IP and IP supervision. However it may suggest that more research combining interprofessional and intercultural learning may contribute to a better understanding of the notion of professions as distinct cultures and students’ perceptions of IPE ‘interculturally’. This may further develop best practice in interprofessional supervision that empowers student learning and reinforces their professional identity.